Prospectus validity and obligation to asupplement (to correct and update) the prospectus - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The paper deals with the two important issues of the law of capital market. Namely, the period of time in which the prospectus is valid (validity) and obligation to asupplement (to correct and update) the prospectus. The Law on the Capital Market of Serbia regulates validity of the prospectus, i. e. the time period in which the prospectus is valid. The prospectus shall be valid for 12 months after its publication for the purposes of the offers of securities to the public or the admission to a regulated market, under the condition that the information in the prospectus, where appropriate, updated by a supplement to the prospectus, containing the latest information on the issuer and securities which shall be offered to the public or admitted to trading on a regulated market or MTF. The paper is particularly focused on the difference between the time of the validity of the prospectus and the period of the validity of public offering of securities. The time for which the prospectus is valid (validity) is an issue which is connected to the obligation to update and supplement the prospectus as well as to the ad hoc obligation to inform the public in the capital market. An obligation to supplement (to update and/or to correct). i. e. to create a supplement to the prospectus exists from the moment the prospectus is approved until the end of the public offering or until the securities are admitted to trading on a regulated market or MTF. An obligation to update and correct the prospectus indicates and obligation to include completely new relevant information in the supplement of the prospectus or to correct the relevant irregularities or incompleteness of information contained in the prospectus with regard the issuer and securities which are to be offered to the public or admitted to trading on a regulated market or MTF, as long as those facts might be of relevance for the investment decision.